Establishing the Omics Nursing Science & Education Network. Issue 2 (6th February 2020) - Tully, Lois A.; Calzone, Kathleen A.; Cashion, Ann K.
Abstract: Purpose: To establish a website to advance nursing research and education involving omics technologies and methodologies through facilitating collaborations, use of existing data and samples, mentoring, and access to training opportunities. Methods: The Omics Nursing Science & Education Network (ONSEN) website was established following identification of gaps in omics nursing infrastructure and resources that could be addressed via a concerted, collaborative effort. ONSEN content was created using input from a workgroup of experts in genomics and other omics, education, practice, and nursing research. Alpha testing was conducted with workgroup members, followed by website refinements and enhancements, and subsequent beta testing by potential end users. ONSEN was launched in August 2018. Findings: ONSEN has three main sections. The Education and Training section provides information on mentoring and pre‐ or postdoctoral opportunities in addition to a knowledge matrix to advance education and skills in genomic nursing science. The Research Collaborations section promotes awareness of ongoing omics nursing research in order to foster collaborations and sharing of samples or data among investigators with programs in omics nursing research or an interest in developing such programs. The Common Data Elements (CDE) section provides information on the benefits of incorporating CDEs into nursing science as well as links to National Institutes of Health resources to facilitate use of CDEs. Conclusions: ONSEN provides opportunities for nurse scientists and trainees to leverage samples and datasets, locate mentors and pre‐ or postdoctoral positions, further the use of CDEs, and enhance education and skills for integrating omics into nursing science. Clinical Relevance: Advancing omics nursing science via ONSEN resources will accelerate the elucidation of the molecular underpinnings of disease and associated symptoms as well as inform the development of rapidly translatable, personalized intervention strategies, grounded in biological mechanisms, for improved health outcomes across populations and the lifespan.